PTU-165 Endoscopic response of oesophageal carcinoma to neo-adjuvant chemotherapy and survival post-oesophagectomy. (28th May 2012) - Jones, A M; Cornish, J; Chan, D; Clark, G
Abstract : Introduction: Endoscopy and biopsy is an essential initial investigation in oesophageal carcinoma. At our unit a repeat endoscopy is conducted after a patient has completed neo-adjuvant chemotherapy and prior to proceeding to oesophagectomy, predominantly to obtain anatomical information. This study aims to determine whether prognostic information can be derived from the response to chemotherapy. Methods: Data were retrospectively collected for patients who had undergone oesophagectomy following neo-adjuvant chemotherapy under a single surgeon over a 10-year period. At endoscopy after chemotherapy, it was noted whether the tumour had made a complete response, a partial response or no response at all, according to length, circumferential involvement and degree of stenosis. Survival data were obtained and compared between groups. Results: 72 patients (60 Male, 12 Female) were identified. 25 patients had no response to neo-adjuvant chemotherapy as assessed endoscopically and had a median survival of 27 months and 2-year survival of 38%. 39 patients showed a partial response endoscopically and had a median survival of 30 months and a 2-year survival of 40%. For the eight patients who had a complete response median survival was 57 months and 2-year survival of 68%. Conclusion: The response to neo-adjuvant chemotherapy as assessed endoscopically is predictive of post-operative prognosis. A larger study is required to determine if endoscopic assessment could be used to select patients unlikely to benefit from surgery. Competing interests: None declared.